PROFIL KETERAMPILAN BERTANYA SISWA PADA PEMBELAJARAN BIOLOGI SMA NEGERI 2 BANDAR LAMPUNG - Fitri Nuraini; Tri Jalmo; Berti Yolida (Universitas Lampung, 2017)
The objectives of this research was to determine the questioning skills and the quality of the questions on biology learning of students from XI and grade XII Science SMAN 2 Bandar Lampung. Samples were grade students from class XI science 1, XI science 7, XI science 8, XII science 6, and XII science 7 which are consisted of 179 students that chosen by using technique simple random sampling. Qualitative data of questioning skill and quality of questions were obtained from observation and analyzed by counting the percentage and interpreted into a table criteria and strengthened by documentation. The results showed that questioning skill of students was